2021
DOI: 10.1159/000512586
|View full text |Cite
|
Sign up to set email alerts
|

Protocol and Baseline Data on Renal Autologous Cell Therapy Injection in Adults with Chronic Kidney Disease Secondary to Congenital Anomalies of the Kidney and Urinary Tract

Abstract: Background: Advanced cell therapies with autologous, homologous cells show promise to affect reparative and restorative changes in the chronic kidney disease (CKD) nephron. We present our protocol and preliminary analysis of an IRB-approved, phase I single-group, open-label trial that tests the safety and efficacy of Renal Autologous Cell Therapy (REACT; NCT 04115345) in adults with congenital anomalies of the kidney and urinary tract (CAKUT). Methods: Adults with surgically corrected CAKUT and CKD stages 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Furthermore, our sample did not include a diverse representation of races. Future work is focusing on global phase III trials, congenital CKD conditions, eGFR inclusion of 50–14 mL/min/1.73 m 2 , and bilateral kidney injections using re-dosing triggers [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our sample did not include a diverse representation of races. Future work is focusing on global phase III trials, congenital CKD conditions, eGFR inclusion of 50–14 mL/min/1.73 m 2 , and bilateral kidney injections using re-dosing triggers [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes will mitigate adverse procedural events, and image guidance will ensure REACT enters the renal cortex. This approach currently is also used in a phase I open label trial of CKD due to congenital anomalies of the urinary tract [24].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, renal autologous cell therapy (REACT) has demonstrated positive clinical outcomes in ADPKD. 75 Unlike stem cell therapy, REACT uses a sorted population of the patient's autologous selected renal tubular cells (SRC) and ongoing trials investigating REACT include NCT04115345, NCT05018416, and NCT02836574. Early findings from NCT02836574 indicated that SRCs can recreate neo-kidney-like tissue at the kidney site, and the therapy led to a decline in eGFR over a 1 year period.…”
Section: Cell Therapies For Genetic Kidney Diseasesmentioning
confidence: 99%